Health risk assessment of fluoride exposure due to groundwater consumption in Romania - Simona Dobrinas; Alina Soceanu; Natalia Manea; Anca Sirbu; Corina Ionela Dumitrescu; Viorica Popescu; Semaghiul Birghila; Nicoleta Matei; Ionela Carazeanu Popovici (IWA Publishing, 2022)
Fluoride has both beneficial and detrimental effects on human health. Concentrations of fluoride less than 1.0 mg/L in ingested water are beneficial for the rate of tooth decay, especially in children. The aims of the paper are as follows: (i) to monitor fluoride concentrations in drinking water samples (well water and tap water from the rural district of Valea Râmnicului, Romania); (ii) to study and select the optimal buffer solution and the optimal volume used in the analyses and (iii) to validate the potentiometric method for determining fluoride ions with a selective ion electrode. The values of fluoride ion concentrations in the groundwater samples and in tap water varied from 0.01 to 0.138 mg/L. The values for the hazard quotient for the studied samples varied from 0.01 to 0.13. HIGHLIGHTS A large part of Romania's population uses water from wells as a source of drinking water.; Monitoring of fluoride in drinking water samples.; Optimization and validation of the potentiometric method for determining fluoride ions with a selective ion electrode.; The performed health risk assessment of fluoride exposure due to groundwater consumption is based on the estimated daily intake (EDI) and the hazard quotient (HQ).;